Use of Nano Magnetic Zirconia Phosphoric Acid as an Efficient and Recyclable Catalyst for the Clean Synthesis of Some Important Quinolone Carboxylic Acid Derivatives - Nakhaei, Ahmad; Farsinejad, Sadaf; Ramezani, Shirin (Current Green Chemistry, 2017)
Background: In this investigation, nano-Fe3O4@ZrO2-H3PO4 (n-FZPA), as a magnetic catalyst for the preparation of some important fluoroquinolones has been reported. Methods: These compounds were synthesized by the two-component reaction of piperazine derivatives or (4aR,7aR)-octahydro-1H-pyrrolo[3,4-b] pyridine with a series of 7-halo-6-fluoroquinolone-3- carboxylic acids upon reflux condition in water as a green solvent. Results: In the final outcomes, it was found that n-FZPA has high catalytic activity for the preparation of fluoroquinolone derivatives in high yield. Besides, the recyclability of this material has been investigated showing that the n-FZPA could be reused at least three times without any change in its catalytic properties. Conclusion: This novel and green catalytic procedure provides quick pathway to the target products upon refluxing water with the simple work128;up procedure, and without the use of dangerous organic solvents.
Keywords: nano-Fe3O4@ZrO2-H3PO4